St. Kitts and Nevis : 'the wind of change is blowing' (1998)
Focuses on the economic and social conditions of St. Kitts and Nevis as the population is about to vote in a referendum that could split the twin-island Federation.
Keywords: ECONOMIC CONDITIONS